Pengaruh Dimensi Kualitas Jasa Terhadap Kepuasan Nasabah (Studi Kasus Pada Bank Syariah Mandiri Kantor Cabang Pembantu Padang Bulan Medan) - Isra Hayati; Yuli Yuli Yanti Siregar (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
The purpose of this study was to determine the dimensions of service quality influencing customer satisfaction at PT. Bank Syariah Mandiri Padang Bulan Sub-Branch Office. The approach of this research used is a quantitative approach. This retrieval technique uses accidental sampling technique with the number of samples studied as many as 25 respondents. Based on the results of the partial test the influence of the Dimensions of Service Quality on Customer Satisfaction obtained tcount of 5.120. Then it can be seen that t count t table is 5.120 1.713. And has a significant number of 0,000 5 0,05. (Sig 0,000 ?0,05) then it can be concluded Ha is accepted and Ho is rejected, this shows that there is a significant influence between the Dimensions of Service Quality on Customer Satisfaction at PT. Bank Syariah Mandiri Padang Bulan Branch. The magnitude of the influence of Service Quality Dimensions on customer loyalty is 49.5% of Customer Satisfaction variables influenced by Service Quality Dimensions. While the remaining 50.5% is influenced by variables or other factors not included in the study.